2022
DOI: 10.1155/2022/6291497
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA CASC2 Facilitated Wound Healing through miRNA‐155/HIF‐1α in Diabetic Foot Ulcers

Abstract: Diabetic foot ulcers (DFU) are among the serious complications which are closely linked to diabetes mellitus. However, there is still a lack of accurate and effective standard prevention and treatment programs for DFU. In this manuscript, we have investigated the function of lncRNA cancer susceptibility candidate 2 (CASC2)/miR-155/hypoxia-inducible factor 1-alpha (HIF-1α) in the wound healing of DFU. We have analyzed lncRNA CASC2`s expression in the marginal tissues of ulcers in patients and mice with DFU. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This dysregulated pathway dampened the migration, proliferation, and collagen production of fibroblasts. 19 Another study reported that in the margin of DFUs miR-29b was downregulated; its upstream lncRNA H19 and downstream FBN1 were upregulated; whereas these changes had positive effects on fibroblast functions, including increased proliferation and migration and decreased apoptosis. 33 It is considered that these changes are attributed to compensatory effects of the body to promote the healing of diabetic chronic wounds.…”
Section: Lncrna/mir Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…This dysregulated pathway dampened the migration, proliferation, and collagen production of fibroblasts. 19 Another study reported that in the margin of DFUs miR-29b was downregulated; its upstream lncRNA H19 and downstream FBN1 were upregulated; whereas these changes had positive effects on fibroblast functions, including increased proliferation and migration and decreased apoptosis. 33 It is considered that these changes are attributed to compensatory effects of the body to promote the healing of diabetic chronic wounds.…”
Section: Lncrna/mir Pathwaysmentioning
confidence: 99%
“…32 Similarly, overexpressed miR-155 in the wound not only inhibits the function of fibroblasts but also further inhibits the expression of VEGF by inhibiting the expression of HIF-1α in fibroblasts. 19 Low expression of miR-21-3p in the wound can increase the expression of its target SPRY1, inhibit the function of fibroblasts and inhibit their secretion of VEGF. 30 After the reduction of HIF-1 by miR-210, the Tips: """: increase, "#": decrease, "-": inhibited, "+": enhanced, "/": have no effect or have not been reported in relevant literature.…”
Section: Vegfmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing HIF-1α level by lncRNAs is considered as an effective strategy to improve healing process. LncRNA-H19 and lncRNA MIR31HG have been employed to regulate the expression of HIF-1α to enhance the proliferation of fibroblast ( 54 ). In addition, lncRNA FAM83A-AS1 involved several signaling pathways such as glycolysis, hypoxia, and OXPHOS signaling.…”
Section: Exosomal Lncrna For Diabetic Wound Healingmentioning
confidence: 99%
“…By contrast, miR-155 overexpression inhibited the function of CASC2[ 75 ]. Another study showed that HIF-1α inhibition reversed the effects of miR-155 downregulation on fibroblasts[ 76 ]. Evidently, lncRNAs have a considerable regulatory role in cellular functions during re-epithelialization and remodeling.…”
Section: Lncrnasmentioning
confidence: 99%